Porcine plasma protein-sugar maillard reaction products (MRPs) : some factors affecting antioxidant activity and their application - Wittayachai Lertittikul (Prince of Songkla University, 2005)
Thesis (M.Sc., Food Technology)--Prince of Songkla University, 2005